Differential expression of metabotropic glutamate and GABA receptors at neocortical glutamatergic and GABAergic axon terminals - Bragina, Luca; Bonifacino, Tiziana; Bassi, Silvia; Milanese, Marco; Bonanno, Giambattista; Conti, Fiorenzo (Frontiers in Cellular Neuroscience, 2015)
Metabotropic glutamate receptors (mGluRs) and GABAB receptors are highly expressed at presynaptic sites. To verify the possibility that the two classes of metabotropic receptors contribute to axon terminals heterogeneity, we studied the localization of mGluR1α, mGluR5, mGluR2/3, mGluR7 and GABAB1 in VGLUT1-, VGLUT2- and VGAT-positive terminals in the cerebral cortex of adult rats. VGLUT1-positive puncta expressed mGluR1α (~5%), mGluR5 (~6%), mGluR2/3 (~22%), mGluR7 (~17%), and GABAB1 (~40%); VGLUT2-positive terminals expressed mGluR1α (~10%), mGluR5 (~11%), mGluR2/3 (~20%), mGluR7 (~28%), and GABAB1 (~25%); whereas VGAT-positive puncta expressed mGluR1α (~27%), mGluR5 (~24%), mGluR2/3 (~38%), mGluR7 (~31%), and GABAB1 (~19%). Control experiments ruled out the possibility that post-synaptic mGluRs and GABAB1 might have significantly biased our results. We also performed functional assays in synaptosomal preparations, and showed that all agonists modify Glu and GABA levels, which return to baseline upon exposure to antagonists. Overall, these findings indicate that mGluR1α, mGluR5, mGluR2/3, mGluR7 and GABAB1 expression differ significantly between glutamatergic and GABAergic axon terminals, and that the robust expression of heteroreceptors may contribute to the homeostatic regulation of the balance between excitation and inhibition.